Instytucja mężów zaufania w polskim prawie wyborczym - Wrzalik, Magdalena (Wydawnictwo Naukowe UAM, 2015)
Instytucja mężów zaufania, często określana mianem „niemych obserwatorów wyborów”, traktowana jest z dużym dystansem i budzi wśród przedstawicieli doktryny prawa konstytucyjnego, jak również świata polityki, wiele wątpliwości. Jej zadaniem jest reprezentowanie podczas wyborów interesu kandydata bądź listy kandydatów przed komisją wyborczą i czuwanie nad prawidłowym przebiegiem czynności wyborczych, w tym zliczaniem głosów i ustalaniem wyników wyborów. Ma zatem istotne znaczenie dla zapewnienia rzetelności i uczciwości procedur wyborczych, jak również poszanowania podstawowych zasad prawa wyborczego, w szczególności zasady powszechności i wolności wyborów oraz tajności głosowania. Niestety w Kodeksie wyborczym uregulowana jest stosunkowo fragmentarycznie, zaś jej dookreślenie stanowią wytyczne Państwowej Komisji Wyborczej. Przed wyborami pojawiają się też różne opracowywane najczęściej przez partie polityczne instrukcje, określane czasem mianem vademecum, czy poradniki dla mężów zaufania, których treść może budzić wątpliwości. Skłania do wniosku o potrzebie debaty przedstawicieli doktryny i polityków nad funkcjami i konstrukcją prawną instytucji mężów zaufania w polskim prawie wyborczym, jak i stosownymi jego zmianami.

The institution of returning officers, often referred to as “silent poll watchers”, is treated with a great measure of detachment and even raises many doubts among constitutional law theorists, as well as in the world of politics. Its task is to represent the interest of a candidate or a list of candidates before the election committee during the election time and to ensure proper conduct of electoral activities, including in particular counting votes and setting for confirmation of the election results. Therefore, it is essential for ensuring reliability and justness of electoral procedures and the proper implementation of fundamental principles of the electoral law; especially the electoral adjectives like the universality and freedom of election, as well as the secrecy of voting. However, in the Electoral Code this institution is relatively marginalized, and its clarification is settled in guidelines issued by the National Electoral Committee. Prior to elections, various elaborations are issued mostly by political parties, sometimes referred to as vade mecum, that is the guidelines for returning officers, the content of which can raise various doubts. It leads to the conclusion that the debate among legal theorists and politicians over the functions and structure of the legal institution of returning officers in the Polish Electoral Law and on its proper amendments should be carried out.
The institution of returning officers in the Polish electoral law
Keywords: mąż zaufania; returning officer; prawo wyborcze; electoral law; komitet wyborczy; election committee